THE STRATEGIC OPENNESS INDEX (SOI) AS A TOOL FOR ENHANCING THE QUALITY OF STRATEGIC DECISION-MAKING IN JOINT-STOCK COMPANIES (Innovations in Science and Technologies, 2025)
This paper introduces the Strategic Openness Index (SOI) — a novel evaluative mechanism designed to measure and improve the quality of strategic decision-making in joint-stock companies. The index is built upon three core pillars: transparency, accountability, and stakeholder inclusivity. Using international evidence and empirical testing in the context of Uzbekistan, the study demonstrates that companies with higher SOI scores exhibit significantly better valuation indicators (Tobin’s Q), reduced strategic risks, and increased investor confidence. This approach advances the governance-performance paradigm by shifting focus from formal decision outcomes to the inclusivity and openness of decision-making processes.